2006
DOI: 10.4269/ajtmh.2006.74.162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites Including Microsporidia in Human Immunodeficiency Virus–infected Adults in Cameroon: A Cross-Sectional Study

Abstract: To assess the prevalence of intestinal parasites in a cohort of human immunodeficiency virus (HIV)-infected adults in Cameroon, a cross-sectional study was conducted. Detection of parasites was performed in 181 stool samples from 154 HIV-infected patients with a mean CD4 cell count of 238 cells/mm(3). Only 35 patients (22%) were receiving antiretroviral therapy at the time of stool sampling, and 46 (29%) had diarrhea. Opportunistic protozoa were found in 15 patients (9.7%), 8 of whom (53%) had diarrhea. Entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
65
10
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 25 publications
(32 reference statements)
20
65
10
4
Order By: Relevance
“…This study was the first epidemiological study in Ahvaz on frequency of microsporidia in 2 groups . These results are very similar to the prevalence found in patients with HIV in Ethiopia with 39 (16%) by PCR and 18(7.6%) by staining that Enterocytozoon bieneusi were 77% (30/39) and Encephalitozoon intestinalis 15.4% (6/39) 29 .In developing countries, prevalence of E.bieneusiis 2.5% -51% 9 in HIV + patients with diarrhea and <5% in patients without diarrhea 36 . In this study E.bieneusi prevalence rates for HIV + patients with diarrhea was 66.7% (16/24) and 29.2% (7/24) for patients without diarrhea, therefore the higher occurrence of E.bieneusi is not surprising.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study was the first epidemiological study in Ahvaz on frequency of microsporidia in 2 groups . These results are very similar to the prevalence found in patients with HIV in Ethiopia with 39 (16%) by PCR and 18(7.6%) by staining that Enterocytozoon bieneusi were 77% (30/39) and Encephalitozoon intestinalis 15.4% (6/39) 29 .In developing countries, prevalence of E.bieneusiis 2.5% -51% 9 in HIV + patients with diarrhea and <5% in patients without diarrhea 36 . In this study E.bieneusi prevalence rates for HIV + patients with diarrhea was 66.7% (16/24) and 29.2% (7/24) for patients without diarrhea, therefore the higher occurrence of E.bieneusi is not surprising.…”
Section: Discussionsupporting
confidence: 76%
“…These findings were supported by others who reported PCR is more sensitive(100%) compared to microscopic techniques in detecting microsporidial infection in HIV + patients 34,49,50 .The increased sensitivity of PCR can be attributed to lower threshold of microsporidia (10 2 spores/g stool) compared to optical microscopy in which the cut-off point ranges from 10 4 to 10 6 spores 51 . Althoughtrichrome staining is are liable and an available technique for detection of microsporidian spores in vitro, detection process is difficult and time-consuming for staining 46,52 .Moreover, higher prevalence of E. bieneusi compared to E. intestinalis has been reported in some studies 29,36,53 . While in one study in Egypt in cancer patients reported that E. intestinalis was the only species identified and the most prevalent in leukemic patients 46 .As shown in other studies, PCR could detect E. intestinalis (20%) and E. hellem (10%) in stool samples taken from cancer patients 20 , while Chabchoub et al found equal prevalence of E. intestinalis and E. hellem (33.3%) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…15 An overall prevalence of 10% of intestinal parasitic infection was observed among diabetic patients which is lower than the prevalence reported in the south western part of Nigeria (18.7%) 8 and South east Turkey (47%). 2 Geographical location may account for this difference as the Olusegun et al 8 study was carried out in Nigeria and the Nazligul et al 2 study was carried out in Sanliurfa province which was an endemic zone for intestinal parasites.…”
Section: Discussionmentioning
confidence: 44%
“…The aetiological agents have been identified in various studies from India and other parts of world includes, E. histolytica, G. lamblia, Cryptosporidium parvum, Isospora belli, Microsporidia, H.nana, Ascaris lumbricoides, Ancylostoma duedonale etc. [3][4][5][6][7][8][9]11,19,20 . .…”
Section: Discussionmentioning
confidence: 99%